PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PEKERTI NUSANTARA - Lestari, Nurlaela Eva Puji; Siti Patimahtu Zahro (The Asia Pacific Journal Of Management Studies, 2024)
This study aims to determine how much influence the work environment and workload have on employee performance at PT Pekerti Nusantara which includes variables (independent) work environment, workload has an influence on employee performance (dependent). The population in the study were all employees totaling 35 people. Sampling data obtained through questionnaires were tested through quantity tests; namely validity and reliability tests and hypothesis testing using multiple linear regression, determination test (R2 ), t test and f test. From the results of multiple linear regression shows that employee performance is influenced by work environment variables b1X1: 0.545, workload variables b2X2: 0.215. The results of the coefficient of determination (R2 ) use an adjusted r square value of 0.775, this indicates that the variables studied work environment variables (X1) and workload variables (X2) have an influence on employee performance (Y) of 75.5% while the remaining 24.5% is influenced by variables not studied. From the results of the t test and f test calculations, it can be seen that all elements of the work environment variable and workload variable together have a positive and significant effect on employee performance variables with a Sig value of 0.000 < 0.05 and an Fcalcute values of 53.480 > Ftable 3.280. For the variable that has the most dominant effect on employee performance variables is the work environment variable